2018
DOI: 10.1002/pbc.27111
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of refractory germ cell tumors in children with paclitaxel, ifosfamide, and carboplatin: A report from the Children's Oncology Group AGCT0521 study

Abstract: TIC is active in relapsed pediatric MGCT and should be considered for salvage therapy in children. In adolescents and older adults with relapse MGCT, TIP or high-dose chemotherapy with stem cell remain the standard therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…This cohort also experienced a reassuring safety profile with paclitaxel, as no patients experienced neurotoxicity or paclitaxel-induced anaphylaxis or severe allergic reactions, and other side effects were seen infrequently. The favorable safety profile seen in this pediatric cohort reassuringly was in line with other pediatric case reports that safely used paclitaxel to treat KS in low- [ 16 ], middle- [ 30 ], and high-income [ 31 ] settings, and to treat other pediatric cancers [ 32 , 33 ]. Similarly, in a large randomized controlled trial of adults with HIV associated KS in LMIC, paclitaxel was well tolerated with a favorable safety profile [ 15 ].…”
Section: Discussionsupporting
confidence: 84%
“…This cohort also experienced a reassuring safety profile with paclitaxel, as no patients experienced neurotoxicity or paclitaxel-induced anaphylaxis or severe allergic reactions, and other side effects were seen infrequently. The favorable safety profile seen in this pediatric cohort reassuringly was in line with other pediatric case reports that safely used paclitaxel to treat KS in low- [ 16 ], middle- [ 30 ], and high-income [ 31 ] settings, and to treat other pediatric cancers [ 32 , 33 ]. Similarly, in a large randomized controlled trial of adults with HIV associated KS in LMIC, paclitaxel was well tolerated with a favorable safety profile [ 15 ].…”
Section: Discussionsupporting
confidence: 84%
“…There is no consensus about this issue in adult series as well. Pashankar et al 11 reported more than 50% of children in PR after two courses of TIP (paclitaxel 135 mg/m 2 /day on day 1, ifosfamide 1800 mg/m 2 on days 1 to 5, and carboplatin with AUC 6.5 on day 1). In our experience, after SLCT based on "ICE," 19 of 21 patients reached PR or CR.…”
Section: F I G U R E 2 Os Of Relapsed and Refractory Patientsmentioning
confidence: 99%
“…Nonetheless, data and experience regarding secondline treatment for relapsed/refractory GCT in the pediatric setting are sparse, especially with regard to long-term outcome. [10][11][12] We present the experience of the Associazione Italiana di Ematologia ed Oncologia Pediatrica (AIEOP) concerning treatment of children with relapsed/refractory malignant GCTs after first-line platinumbased chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The conditioning in the French cohort was based on etoposide–thiotepa in five cases and carboPEC in four patients [ 15 , 16 ]. The Children’s Oncology Group (COG) group used a paclitaxel, ifosfamide, and carboplatin (TIC) regimen (paclitaxel 135 mg/m 2 /day on day 1, ifosfamide 1800 mg/m 2 /dose on days 1–5, and carboplatin with area under curve (AUC) 6.5 on day 1) as a second-line therapy in children with relapsed GCT and reported that the overall response rate was 44% using combined Response Evaluation Criteria in Solid Tumors (RECIST) response and tumor marker decline [ 17 ]. In this study, ACST was performed in five patients; however, only one of five patients was cured, and no details on the HDCT regimen were provided.…”
Section: Discussionmentioning
confidence: 99%